Q. 275.0( 2 Votes )

# Find the value of

Answer :

Given quadratic equation, (2p + 1) x2 - (7p + 2) x + (7p – 3) = 0

Comparing the given equation with ax2 + bx + c = 0, we get

a = (2p + 1), b = -(7p + 2), c = (7p – 3)

We know that a quadratic equation ax2 + bx + c = 0 has equal roots (i.e., coincident roots), if b2 – 4ac = 0.

(-(7p + 2))2 – 4(2p + 1) (7p - 3) = 0

49p2 + 28p + 4 – 56p2 + 24p – 28p + 12 = 0

-7p2 + 24p + 16 = 0

7p2 - 24p - 16 = 0

By factorization method,

7p2 – 28p + 4p – 16 = 0

7p (p – 4) + 4(p – 4) = 0

(p – 4) (7p + 4) = 0

(p - 4) = 0 (or) (7p + 4) = 0

p = 4 (or) p = -4/7

For equal roots, roots = Roots = Case 1: When p = 4

Roots = (7(4) + 2)/2(2(4) + 1)

= 30/18

= 5/3, 5/3

Case 2: When p = -4/7

Roots = (7(-4/7) + 2)/2(2(-4/7) + 1)

= -2/(-2/7)

= 7, 7

The value of p is 4 or -4/7. The roots are 5/3, 5/3 or 7, 7.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 